Existence Results for Fractional Differential Equations with the Riesz-Caputo Derivative (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we apply some fixed point theorems to attain theexistence of solutions for fractional differential equations with the space-timeRiesz-Caputo derivative. We study the boundary value problems that thenonlinearity term $f$ is relevant to fractional integral and fractional derivative.In addition, the boundary conditions involve integral. Two examples are givento show the effectiveness of theoretical results.